USAHA CREW DALAM MENGELOLA PROGRAM UNGGULAN BAGURAU DI UDARO DI RADIO LUHAK NAN TUO - Putra, Ade; Irman, Irman (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
The main problem in this research is the management of the superior bagurau program on air on Radio Luhak Nan Tuo. This research aims to describe the efforts of the Luhak Nan Tuo radio crew in managing the superior program bagurau on air. The research uses a qualitative descriptive method, namely explaining objectively about the crew's efforts in managing the Bagurau diudaro program. Data collection was carried out by analyzing interview data with broadcasters and program directors, observation and documentation in the field and drawing conclusions. Based on the research results, it can be concluded that CrewRadio Luhak Nan Tuo, in implementing the program so that it does not deviate and remains popular with the public, the crew manages the program using broadcast management. Broadcasting management includes Planning, Organizing, Actuating, Supervision.